Recurrent carbon labels induce bipartisan effects in environmental choices under risk - Zahra Rahmani Azad; Doron Cohen; Ulf J. J. Hahnel (Judgment and Decision Making)
Addressing climate change requires substantial shifts in individual behavior. Providing information about climate externalities through carbon labels is a promising tool to foster sustainable choices when individuals weigh environmental against personal outcomes. We study the impact of carbon labels over time and their underlying mechanisms in a repeated risky choice task. We ran two preregistered experiments (US samples, N = 1,268) with realized carbon and monetary payoffs, examining how choice is influenced by the timing of carbon information (One-off vs. Recurring) and participants’ political preference (i.e., Democrat or Republican voters). In Study 1, we find that both Democrats and Republicans reduce carbon emissions when carbon labels were provided. Further, recurring labels significantly reduced carbon choices compared to one-off labels. Study 2 replicated the results in a within-participant design and showed that the impact of recurring carbon labels on sustainable choices cannot be explained by the strength of emission recall. This suggests that recurring labels amplify the importance given to the climate attribute in the decision process, operating via attentional rather than informational mechanisms. Our results emphasize the importance of providing climate externality information at time of use to raise awareness about climate costs and bolster sustainable preferences across population segments.